2020
DOI: 10.1136/oemed-2019-106074
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal trends in respirable dust and respirable quartz concentrations within the European industrial minerals sector over a 15-year period (2002–2016)

Abstract: ObjectivesSince 2000 the European Industrial Minerals Association’s Dust Monitoring Programme (IMA-DMP) has systematically collected respirable dust and respirable quartz measurements from 35 companies producing industrial minerals. The IMA-DMP initiative allowed for estimating overall temporal trends in exposure concentrations for the years 2002–2016 and for presenting these trends by type of mineral produced, by jobs performed and by time of enrolment into the DMP.MethodsApproximately 32 000 personal exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…An initial literature review and environmental scan revealed related similar types of services such as on-line qualitative exposure control plan generators (e.g., Center for Protection of Worker Rights ( 18 ), task-specific exposure duration guidelines ( 19 ), “first tier” REACH tools ( 20 ) and higher-level surveillance efforts such as the European Industrial Minerals Association's “Dust Monitoring Programme” in Europe ( 21 ). None of the available tools satisfied the specific requirements of the BC situation, leaving a knowledge gap, and an opportunity for development of an end-user exposure data management tool.…”
Section: Contextmentioning
confidence: 99%
“…An initial literature review and environmental scan revealed related similar types of services such as on-line qualitative exposure control plan generators (e.g., Center for Protection of Worker Rights ( 18 ), task-specific exposure duration guidelines ( 19 ), “first tier” REACH tools ( 20 ) and higher-level surveillance efforts such as the European Industrial Minerals Association's “Dust Monitoring Programme” in Europe ( 21 ). None of the available tools satisfied the specific requirements of the BC situation, leaving a knowledge gap, and an opportunity for development of an end-user exposure data management tool.…”
Section: Contextmentioning
confidence: 99%
“…9 The Industrial Minerals Association-Dust Monitoring Programme, has been ongoing since 2000 and provides quantitative insights into differences in respirable dust and quartz exposures between middle-income and high-income countries. 10 In the SYNERGY project, time-specific, job-specific and regionspecific quantitative exposure levels for four carcinogens (asbestos, chromium-VI, nickel and quartz) were estimated based on thousands of personal measurements collected in Europe and Canada. 11 Exposure information collected in general population case-control studies and cohort studies have been used to develop (population-specific) job exposure matrices and could also be used to develop more precise estimates of exposure prevalence by industry.…”
Section: Proportions Exposed and Level Of Exposurementioning
confidence: 99%
“…17 Differences in measured respirable crystalline silica across countries provide another illustrative example of the same concept. Zilaout and colleagues 10 analysed almost 26 000 respirable dust and 23 000 respirable quartz measurements from 35 industrial mineral companies from 154 sites located in 23 countries (19 high-income and 4 middle-income countries) collected between 2002 and 2016. Geometric mean respirable dust concentrations per job per site over time varied over three orders of magnitude from 0.01 to 10 mg/ m 3 .…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations